Cold plasma processing improved the extraction of xylooligosaccharides from dietary fibers of rice and corn bran with enhanced in-vitro digestibility and anti-inflammatory responses. (June 2022) - Mehta, Deepak; Purohit, Anjali; Bajarh, Pooja; Yadav, Kamlendra; Shivhare, U.S.; Yadav, Sudesh Kumar
Abstract: Here, the impact of cold plasma on extraction of xylooligosaccharides (XOS) from rice and corn bran dietary fibers was investigated. Prior to extraction of XOS, polyphenol and dietary fibers were separated from rice and corn bran. Upon cold plasma, the observed changes in the structure of rice and corn bran dietary fibers through FTIR analysis documented their suitability for XOS extraction. Cold plasma treatment was observed to significantly ( p  < 0.05) improve the extraction of XOS from rice and corn bran dietary fibers as compared to untreated. Moreover, SEM images showed micro-punctures in rice and corn bran dietary fibers upon cold plasma treatment. Furthermore, XOS extracted through cold plasma treatment showed better gastric digestion. Also, the cold plasma extracted XOS showed no cytotoxicity against RAW 264.7 and HepG2 cell lines. Cold plasma extracted XOS were observed to improve the anti-inflammatory responses. Industrial relevancy: Now-a-days, fast pace lifestyle demands attention for extraction of nutraceutical compounds like XOS and resource utilization of industrial biomass for extraction of value-added products is need of the hour. Industries are trying to extract these value-added biomolecules but the procedure of extracting these compounds is expensive as well as extensive. Therefore, there is need of powerful and clean technology for extracting such compounds. Cold plasma is one of such technologies which consumes very less energy for efficient breakdown of cell walls to release their valuable compounds. In this regard, present study documented the use of cold plasma processing in the extraction of XOS, useful prebiotics from the industrial by-products rice and corn bran. Hence, the technology documented the utilization of industrial waste biomass for the efficient recovery of XOS with better qualities. Graphical abstract: Unlabelled Image Highlights: Cold plasma enhanced the enzymatic hydrolysis of dietary fiber from rice and corn bran. Cold plasma enhanced extraction of XOS from rice and corn dietary fiber. Cold plasma enhanced the in-vitro gastric digestibility of extracted XOS. Cold plasma extracted XOS had no cytotoxicity towards RAW 264.7 and HepG2 cell lines. Cold plasma extracted XOS show improved anti-inflammatory responses.